The Effect of Kinesiotaping and Nerve Glide Exercise on Wrist Functional Activity in Carpal Tunnel Syndrome Patients at Citama Hospital Bogor Regency 2025 - salim, johanes; Ramadhan, Iqbal; Nasution, Rabiatun (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Carpal tunnel syndrome is a common condition affecting peripheral nerves, causing pain, numbness, tingling, and weakness in the hand and wrist. This occurs when increased pressure develops within the wrist compartment that houses tendons and nerves. When pressure rises, it compresses the median nerve. This nerve innervates the thumb, index finger, middle finger, and half of the ring finger, so clinical manifestations appear in these areas. This condition can be acute or chronic, but chronic cases are more commonly found. Research Objective: To determine whether kinesiotaping and nerve glide exercise have an effect on the functional activity of the hand in patients with carpal tunnel syndrome. Research Method: This study used a quasi-experimental design with a pretest and post-test one-group design. Observation was utilized to measure the functional activity scale of the wrist before and after the application of kinesiotaping and nerve glide exercise. The sample consisted of 12 respondents. The intervention was administered twice a week for 2 weeks. Results: Analysis using the paired T-test on the effects of kinesiotaping and nerve glide exercise yielded a value of p = 0.002 (p < 0.05). This indicates a significant change in the functional activity scale of the wrist in carpal tunnel syndrome patients before and after the intervention of kinesiotaping and nerve glide exercise. The findings conclude that kinesiotaping and nerve glide exercise